PERCEIVED BODY IMAGE AND ITS RELATIONSHIP WITH BODY MASS INDEX, SELF-ESTEEM, BODY CHANGE STRATEGY, AND SOCIAL NETWORK USAGE AMONG RURAL ADOLESCENTS IN SARAWAK, MALAYSIA - Tung, Wong Liang; Rahman, Md Mizanur (2021)
Body image is a complex and multifaceted construct with multiple associated factors determining its perception among adolescents. This study aimed to determine the perceived body imageand its relationship with body mass index, self-esteem, body change strategy, and social network usage among rural adolescents. This study was a cross-sectional study design using a multistage random sampling technique to select adolescentsaged 10 to 19 years. A total of 318 adolescents’ data were collected using a self-administered questionnaire. Data analysis was done using SPSS version 22.0 with a p-value of <0.05 was considered statistically significant. The mean (SD) age of adolescents was 14.6 (2.7)years with a male and female ratio of 1.09:1. The mean score (SD) of perceived body image was 3.63 (0.87). Multiple linear regression analysis revealed that gender, body mass index,and strategy to increase weight couldpredict perceived body image among adolescents. However, self-esteem did not correlate with perceived body image. Although, the body image dissatisfaction level was low among rural adolescents compared to other studies in Malaysia. However, it can still pose a threat to adolescents’ health if not addressed accordingly.